2007
DOI: 10.1016/j.cplett.2007.07.099
|View full text |Cite
|
Sign up to set email alerts
|

OH yields from the CH3CO+O2 reaction using an internal standard

Abstract: Laser flash photolysis of CH 3 C(O)OH at 248 nm was used to create equal zero time yields of CH 3 CO and OH. The absolute OH yield from the CH 3 CO + O 2 (+M) reaction was determined by following the OH temporal profile using the zero time OH concentration as an internal standard. The OH yield from CH 3 CO + O 2 (+M) was observed to decrease with increasing pressure with an extrapolated zero pressure yield close to unity (1.1 ± 0.2, quoted uncertainties correspond to 95% confidence limits).The results are in q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
60
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 22 publications
12
60
2
Order By: Relevance
“…A similar disparity in the experimentally determined OH yields was seen for the analogous CH 3 CO + O 2 reaction [5,[13][14][15][16]. In our prior study [5], we established significantly smaller OH yields using the DF method compared with the PLP results of Blitz et al [13].…”
Section: Pressure Dependence Of the Oh Yield For C 2 H 5 Co + Osupporting
confidence: 69%
“…A similar disparity in the experimentally determined OH yields was seen for the analogous CH 3 CO + O 2 reaction [5,[13][14][15][16]. In our prior study [5], we established significantly smaller OH yields using the DF method compared with the PLP results of Blitz et al [13].…”
Section: Pressure Dependence Of the Oh Yield For C 2 H 5 Co + Osupporting
confidence: 69%
“…24,31,[36][37][38][39] The CH3OCH2 or OH radical precursor(s), reactant (O2), and buffer gas (He or N2) were premixed in a mixing manifold before being flowed through the reaction cell.…”
Section: Methodsmentioning
confidence: 99%
“…The values listed were taken from the reviews of Lightfoot et al, [32] Tyndall et al [33] and Atkinson et al, [26] except for Reaction (R12), which will be discussed below. Recent measurements by Tyndall et al [34] and Carr et al [35] have shown that the reaction of CH 3 CO with O 2 produces OH in one channel with a yield close to unity at zero pressure [Reaction (R4a)]:…”
Section: Computer Simulationsmentioning
confidence: 99%